Primary paraganglioma of the facial nerve: a diagnostic challenge (2023)
ABSTRACT: Paragangliomas are benign tumors of gradual growth that arise from the paraganglion system. They consist of cellular assemblies associated with vascular and neuronal adventitia throughout the body. Moreover, tympanojugular and tympanic PGs are the most common in the head and neck. Primary paraganglioma arising from the facial nerve canal (FN) is rare and challenging to be surgically removed as it is a highly vascularized tumor. Therefore, a preoperative differential diagnosis of an FN tumor is essential for adequate surgical and functional management